La modelización en la enseñanza de las ciencias: criterios de demarcación y estudio de caso - Aragón-Núñez, Lourdes; Jiménez-Tenorio, Natalia; Oliva-Martínez, José María; Aragón-Méndez, Maria del Mar (Revista Científica, 2018)
This paper presents, first different characteristic elements based on the approach of educational modelling throughout a bibliography review. Secondly, a didactic proposal consisting of a total of 29 activities was analyzed. This proposal was proposed for the study of Sun and Earth but specially in the seasons phenomenon, with teachers in starting level from primary school. The experience tried to demonstrate, how the following design would be integrated in to the education by modelling, and in consequence extract the weaknesses and strength to improve the contents and its structure.